Institutions, governance and sustainability in the Colombian policy for municipal territorial ordering - Arias Arbeláez, Fabio Alberto; Vargas, Gloria María (Sociedad y Economía, 2010)
The Colombian policy for municipal territorial ordering, because of its multidimensional character and long term planning, is an institution that allows to investigate the practice of sustainable development in the country. The 388 law of 1997 creates a governance system for municipal planning of territorial ordering with the objective to identify strategic actions for the socioeconomic development and management of natural resources. In this paper a conceptual model is presented based on the new institutionalism in order to analyze this public policy and its relation to sustainable development.